The therapeutic effect of Berberine on rodent models of kidney injury: a systematic review and meta - analysis - Weixiong Xu; ChaoLan Fang; Ming Jian Jiang (BMC Nephrology)
Abstract Background Berberine, a potent bioactive compound extracted from the traditional herbal medicine Huanglian (Coptis chinensis), has garnered significant attention due to its diverse pharmacological effects, particularly in the treatment of renal diseases. Previous studies have highlighted berberine’s therapeutic potential in ameliorating acute kidney injury (AKI) in murine animal models, suggesting its prospective use as a renal protective agent. Its mechanisms involve antioxidant and anti-inflammatory pathways, which are key to its effects. Methods This systematic review and meta-analysis aimed to elucidate the effects and underlying biological mechanisms of berberine in murine models of AKI. To ensure comprehensive coverage, an exhaustive literature search was conducted across reputable databases, including PubMed, Web of Science, Cochrane Library, Ovid, and Embase. The search was performed in December 2024 and no limitations were applied regarding the publication date of the studies. The SYRCLE’s risk of bias tool was employed for a rigorous quality assessment of each study. Statistical analyses were performed using Revman5.4.2 and STATA 15.1 software to ensure the accuracy and reliability of data interpretation. Results We included a total of 19 relevant studies, Our research indicates that the animal studies included in our review demonstrate a significant improvement in renal function metrics of blood specimens in rodent models. The standard mean difference (SMD) for blood urea nitrogen (BUN) is − 3.31 (95% CI: − 4.19, − 2.42), and for Serum Creatinine (SCR) it’s − 2.67 (95% CI: − 3.26, − 2.09), highlighting berberine’s significant renal protective effects. Additionally, berberine favorably affects inflammatory markers, with SMD for IL − 18 at − 1.30 (95% CI: − 2.76, − 0.16) and for TNF - α at − 3.90 (95% CI: − 6.19, − 1.61).Berberine significantly reduced BUN and SCR. Conclusion The beneficial effects of berberine in AKI are likely attributed to its diverse mechanisms, including antioxidant, anti-inflammatory pathways. However, to accurately delineate the efficacy and safety of berberine as a therapeutic intervention for AKI, future research should prioritize large-scale, long-term, and high-quality preclinical trials. Such endeavors are critical for validating our findings and establishing a solid foundation for clinical applications.